A linguagem fotográfica no ensino de Geografia: uma sequência didática para o estudo da cidade - Nascimento, Devid Hallyson da Silva (2021)
This research considers Photography as a language to be used for the study of the city, in particular, Macaíba/RN, in the context of a didactic sequence for teaching-learning, to mobilize pedagogical experiences between students, the city and its landscapes. In this way, the landscape is understood as a "cutout" that shapes the outside world in a determined space and time of our perception, mobilizing pedagogical experiences between students and the city, in a permanent dialogue with the phenomenological method. Therefore, the objective was to propose a Didactic Sequence through photographic narratives that allow experiences with the city. From this walking, narrative and photographing experience, we sought to understand the pedagogical possibilities of the city, understanding it as a space for experimentation. Regarding the specific objectives, we sought to reflect and understand the photographic narrative as a sensory and spatiotemporal language, the didactic sequence as a possibility and methodological strategy for teaching and learning, and the city as a space for experimental strategy; experience the city space of Macaíba/RN, as a laboratory for the creation of photographic narratives that emerge in the construction of a Didactic Sequence; and, finally, taking the city as an educational and experimental space. To give substance to our field of study, we moved to investigate how the topic is approached in classrooms, through the application of an online questionnaire and the analysis of the guiding document for Elementary Education (BNCC). In dialogue with the phenomenological method, we made use of empirical observation, logbooks, photographic records and fieldwork, in order to create a pedagogical premise based on our experience with the city space. Authors such as Calvino (1972), Hillman (1993), Cazetta and Oliveira (2013), Callai (2005), Cavalcanti (2002; 2013), Dantas (2011), Dardel (2011), Fernandez (2008; 2013), Larrosa (2017) and Barthes (1984) made it possible to delimit the paths that supported the course of this educational practice, by discussing the relationship between photography and the teaching of Geography for the study of the city. Finally, the production of images in the city of Macaíba/RN was configured as a means to embody the didactic sequence, designed to be developed with 6th and 7th grade Elementary School II classes, as an educational possibility for the study of the city in Geography classes. In this walker-photographer experience, it was possible to confirm that the city offers countless forms of reading, existing for each subject who observes it in different ways, and photography can be a means, a language to reveal the educability present in the city. In this way, the didactic sequence, the city and the photographs are confused, becoming a single structure, a product of the look from the experience with the city, where, with the body in motion, it becomes capable of perceiving the landscape through multiple senses, through different points of view.